2018
DOI: 10.1186/s12913-018-3314-4
|View full text |Cite
|
Sign up to set email alerts
|

Core knowledge translation competencies: a scoping review

Abstract: BackgroundKnowledge translation (KT) is the broad range of activities aimed at supporting the use of research findings leading to evidence-based practice (EBP) and policy. Recommendations have been made that capacity building efforts be established to support individuals to enact KT. In this study, we summarized existing knowledge on KT competencies to provide a foundation for such capacity building efforts and to inform policy and research. Our research questions were “What are the core KT competencies needed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
97
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(123 citation statements)
references
References 57 publications
7
97
0
2
Order By: Relevance
“…It stands to reason that a topic deserving further exploration is how building institutional capacity is reinforced by paying attention to the capacity of individuals and groups within institutions. In relation to the skills (i.e., impact competencies; Bayley, Phipps, Batac, & Stevens, 2018;Bayley & Phipps, 2019b;Mallidou, Atherton, Chan, Frisch, Glegg, & Scarrow, 2018) and knowledge (i.e., impact literacy; Bayley & Phipps, 2019a, 2019b needed to support impact, future studies could explore how individual and institutional impact competencies and literacies can work synergistically to support impact pathways.…”
Section: Discussionmentioning
confidence: 99%
“…It stands to reason that a topic deserving further exploration is how building institutional capacity is reinforced by paying attention to the capacity of individuals and groups within institutions. In relation to the skills (i.e., impact competencies; Bayley, Phipps, Batac, & Stevens, 2018;Bayley & Phipps, 2019b;Mallidou, Atherton, Chan, Frisch, Glegg, & Scarrow, 2018) and knowledge (i.e., impact literacy; Bayley & Phipps, 2019a, 2019b needed to support impact, future studies could explore how individual and institutional impact competencies and literacies can work synergistically to support impact pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Researchers and practitioners agree that disseminating research through publications and conference presentations may not be enough to change practice in meaningful and sustainable ways (Bennett et al, 2018). Several theoretical and pragmatic methods to narrow the evidence gap have been developed, and although these models require competencies that include research literacy (e.g., skills in research and EBP processes, resources, and dissemination methods), understanding data synthesis and application across various settings and populations (e.g., empirical research; annual, technical, and project reports; white papers; organizational documents), and a lifelong commitment to collaboratively share knowledge and foster innovation in one's unique practice context (Mallidou et al, 2018), few offer clear application processes to facilitate KT. The development of competencies alone may be insufficient to make research accessible to practitioners (Lencucha et al, 2007).…”
Section: Challenges In Translating Evidencementioning
confidence: 99%
“…The gap between what is known, how it is disseminated and absorbed, and what is done in practice has a significant impact on service delivery outcomes (Davis et al, 2003). Occupational therapy practitioners are at risk of using interventions that are unnecessary, are contraindicated, or lack sufficient evidence and of missing opportunities to introduce interventions that can more effectively, efficiently, or predictably improve clients' participation and performance (Mallidou et al, 2018).…”
mentioning
confidence: 99%
“…We conducted a qualitative study with participants and academic institutions in 6 countries (Bangladesh, DRC, Ethiopia, India, Indonesia, and Nigeria) and found that soft-skills, robust networks, and alignment between institutional priorities and incentives are important factors that shape institutional capacity to conduct KT activities in LMICs (9). While strategies such as trainings, mentorship, and institutional leadership engagement have been developed to address these barriers and speci c factors (10,11), these strategies have been mostly applied to academic institutions in highincome countries (HICs) (12)(13)(14) with limited empirical evidence of their effectiveness in LMIC settings (15).…”
Section: Introductionmentioning
confidence: 99%